2015
DOI: 10.1021/acsphotonics.5b00301
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Organization in Dipolar Dye-Based Organic Nanoparticles Probed by Second-Harmonic Scattering

Abstract: We have undertaken polarization-resolved SHS experiments to investigate a series of two fluorescent organic nanoparticles (FONs) made from dipolar dyes bearing a triphenylamine-donating end-group and a slightly hydrophilic acceptor end-group. The FONs, which show very large negative surface potentials, responsible for their good colloidal stability in water, are very bright SHS emitters in water, attractive for single-particle tracking and bioimaging. With the polarization-resolved SHS technique, we come up wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…Indeed, replacing H 2 O with D 2 O caused a 50 and 37% increase in the emission quantum yield Φ f for p‐BDZ and c‐BDZ FONs, respectively, confirmed by a similar increase in the intensity averaged lifetimes of the excited states (33 and 22%, respectively) (Figure S4 and Table S2, Supporting Information). We can thus conclude on strong cohesion of a water shell around the protic FONs and suspect that similar results would apply to any kind of polar FONs, since local organization of water molecules has recently been evidenced by nonlinear hyper‐Rayleigh measurements …”
Section: Results and Dicussionsupporting
confidence: 65%
“…Indeed, replacing H 2 O with D 2 O caused a 50 and 37% increase in the emission quantum yield Φ f for p‐BDZ and c‐BDZ FONs, respectively, confirmed by a similar increase in the intensity averaged lifetimes of the excited states (33 and 22%, respectively) (Figure S4 and Table S2, Supporting Information). We can thus conclude on strong cohesion of a water shell around the protic FONs and suspect that similar results would apply to any kind of polar FONs, since local organization of water molecules has recently been evidenced by nonlinear hyper‐Rayleigh measurements …”
Section: Results and Dicussionsupporting
confidence: 65%
“…[32][33][34][35] Recently, it was reported that triphenylmethane-based nanoparticles are excellent candidates for single particle tracking and bioimaging due to their enhanced fluorescence and second harmonic signal. [36][37][38] Molecular-based nanomaterials such as nanoGUMBOS offer a new route for designing nonlinear optical probes by combining the inherent molecular nonlinear susceptibilities with the ability to control the resulting nanoparticle size as well as molecular interactions and structural ordering.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have investigated the effect of the introduction of bromine (series II ) or tert -butylphenyl (series III ) substituent at the available para positions of the two terminal phenyl groups. This was aimed at both tuning the photophysical properties (by slight modulations of the donating strength) and modulating the colloidal and structural of the subsequent FONs by controlling interchromophoric interactions [12]. Concerning the acceptor moiety, three different acceptors of increasing electron-withdrawing strength have been used: formyl (CHO), dicyanovinyl (DCV) and 1,3-diethyl-2-thiobarbiturate (DETB).…”
Section: Resultsmentioning
confidence: 99%
“…All FONs made from push-pull derivatives I – IIIa – c display a highly negative surface potential, down to −85 mV for FONs made from dye IIa . The highly negative surface of the FONs suggests that the dipolar dyes show specific arrangement and short distance order near the surface [12], with most probably electron-withdrawing groups (which bear O or N atoms having lone pairs and liable to be H-bond acceptors) pointing towards the water interface. These highly negative surface potential values are favorable features in view of the colloidal stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation